Analysis Of Hexavalent Chromium Metal Content Of River Water By Flame Atomic Absorption Spectrophotometer - Atina Atina; Suci Permata Sari (Universitas PGRI Palembang, 2024)
Population growth and intensified human activities have resulted in global environmental conditions experiencing increased risks to water quality. One of the serious threats to water quality is heavy metal contamination, including hexavalent chromium metal (Cr-VI). This study aims to analyze the levels of hexavalent chromium metal (Cr-VI) in river water with an analytical method that is in accordance with SNI 6989.53: 2010, the test method using an atomic absorption spectrometer (SSA)-Nyala. Based on the analysis that has been done on 2 samples (sample A and sample B), the value of hexavalent chromium levels in sample A is 0.035 mg/L and sample B is 0.0127 mg/L. So that the results can be stated that the hexavalent chromium (Cr-VI) levels in the river water are still below the quality standards based on PP RI No. 22 of 2021 concerning the Implementation of Environmental Protection and Management so that it is categorized as safe.